Airway Management in Pierre Robin Sequence: Patterns of Practice. (May 2014) - Collins, Benjamin; Powitzky, Rosser; Robledo, Candace; Rose, Christopher; Glade, Robert
Objectives: To report survey results from American Cleft Palate–Craniofacial Association members on the practice patterns of airway obstruction management in patients with Pierre Robin sequence. Design: A 10-question online survey was sent and the data were reviewed. Setting: Online survey of members of the American Cleft Palate–Craniofacial Association. Patients: Surveys assessed management patterns of patients with Pierre Robin sequence whom a surgeon member of the American Cleft Palate–Craniofacial Association treated for airway obstruction. Interventions: The survey comprised data on management strategies for airway obstruction in Pierre Robin sequence, including tracheostomy, tongue-lip adhesion, mandibular distraction, and treatments that falls in the "other" category. Results: A total of 87 American Cleft Palate–Craniofacial Association members completed the survey. Respondents' results were analyzed as a whole and by individual subspecialty: plastic surgery (n = 33), oromaxillofacial surgery (n = 21), and otolaryngology (n = 29). Although most of the surgeons were trained to manage airway obstruction in Pierre Robin sequence patients using tracheostomy (47%, n = 39) and tongue-lip adhesion (31%, n = 26), 48% reported a current preference for mandibular distraction (n = 40). Of surgeons who preferred to manage Pierre Robin sequence with tongue-lip adhesion (n = 23), 65% were trained to do so (n = 15). Surgeons preferring mandibular distraction (n = 40) and tracheostomy (n = 14) more often reported they were trained to manage Pierre Robin sequence with tracheostomy. Conclusions: Currently there are various practice patterns for the management of airway obstruction in Pierre Robin sequence. Training habits and subspecialty category may influence a surgeon's preference in patients who fail conservative therapy. Treatment guidelines are lacking and may require significant collaboration among centers and subspecialties to develop a more standardized approach to a challenging clinical entity.